Analisis Peran Guru dalam Meningkatkan Minat Baca Siswa SD - Aatikah Sandra; Denaya Gumala Chalis; Tiara Permata Sari; Nur Azmi Alwi; Yarisda Ningsih (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This article delves into the challenges of low reading interest and comprehension skills among primary school students, emphasizing the need for collaborative efforts to address these issues. Reading interest plays a pivotal role in academic development, making its enhancement a shared responsibility among students, teachers, and parents. Through a comprehensive literature review of relevant journals sourced from Google Scholar, the article identifies effective strategies to foster reading interest and improve comprehension skills. Key findings suggest that employing engaging instructional techniques can significantly boost students' reading interest and comprehension abilities. Additionally, cultivating reading habits from an early age by providing appealing reading materials has been shown to establish lasting reading habits into adulthood. Proficient reading skills not only broaden knowledge but also stimulate imagination and creativity. Consequently, educators are encouraged to actively implement effective reading strategies to support literacy development in primary schools.